Inflammasomes: Clinical and Therapeutic Implications (Experientia Supplementum,, 2018)
This volume focuses on the role of inflammasomes in a variety of diseases and their therapeutic options. It gives an overview of the current studies elucidating the molecular implications in the medical and clinical contexts. It covers inflammasomes as potential therapeutic targets and evaluates the benefits of inflammasome inhibitors. .